RANCANG BANGUN SISTEM KEAMANAN PINTU RUMAH DENGAN VOICE RECOGNITION DAN RFID GELANG BERBASIS IOT - Zulkarnaen Zulkarnaen; Al Koriah Al Koriah (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2024)
This research designs and builds a home door security system using voice recognition and Radio Frequency Identification (RFID) technology based on the Internet of Things (IoT). The system combines voice recognition for homeowners and RFID wristbands for authorized users, integrated with an Arduino Uno microcontroller and ESP8266 module for IoT connectivity. The I2C LCD screen displays the system status, and the relays and solenoid door lock control the door lock mechanism. In the voice recognition mode, the door can be controlled with pre-programmed voice commands, while in the RFID mode, the user can open and lock the door by bringing the registered RFID wristband closer. Door status notifications are sent through the Blynk app for real-time remote monitoring. Test results show that the system can identify voice commands and RFID cards with high accuracy, and control door locks effectively. The integration of IoT enables remote monitoring and control of door access, improving the security and comfort of home residents